2016
DOI: 10.1007/s00405-016-3947-z
|View full text |Cite
|
Sign up to set email alerts
|

Residual dizziness after the first BPPV episode: role of otolithic function and of a delayed diagnosis

Abstract: Residual dizziness (RD) following the resolution of a benign paroxysmal positional vertigo (BBPV) episode is frequently reported by patients. Possible causes are still under debate in the literature. This study discusses the possible role of otolithic function and of elapsed time from onset of symptoms to diagnosis in the genesis of RD. In total, 116 patients younger than 65 years with their first episode of BPPV and without any other comorbidities were enrolled in the study. Before a bedside examination, subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 24 publications
3
54
2
4
Order By: Relevance
“…A larger case-control study in the future is needed to verify this finding. The findings of more frequent RD in patients with short (≤4 days) symptom durations in our study were different from previous studies (11, 18, 2729). We assumed that symptom durations may not be the sole factor in the development of RD.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A larger case-control study in the future is needed to verify this finding. The findings of more frequent RD in patients with short (≤4 days) symptom durations in our study were different from previous studies (11, 18, 2729). We assumed that symptom durations may not be the sole factor in the development of RD.…”
Section: Discussioncontrasting
confidence: 99%
“…Risk factors, including aging, a long symptom duration, and anxiety were previously proposed, but study results are conflicting (10, 18, 2731). Optimal management of RD remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17-20 Moreover, at the diagnosis, RD seems not to be related with involved canal, gender, number of repositioning maneuvers or severity of nystagmus, 17-20 and the main causal factor seems to be linked to the duration of vertigo before successful repositioning maneuvers. 17,20,21 There is no agreement about the correlation between RD and duration of BPPV 18 as well on the incidence of RD in migraineurs 20 generally the mean age of patients affected by BPPV and migraine is lower than a control group of not migraineurs. 22,23 RD after BPPV episode is a common condition among the elderly.…”
Section: Resultsmentioning
confidence: 99%
“…These alterations appeared to be rapidly reversible and in these cases the otolith dysfunction could explain only brief dizziness after CRP, but not delayed RD after one week. 21 In 2006 Von Brevern et al demonstrated that a documented otolith dysfunction in patients affected by idiopathic BPPV might account for transient mild imbalance experienced after the resolution of the acute vertigo. In their study the otolith function of patients was tested 1 week and 1 month after successful treatment and compared with 24 healthy subjects.…”
Section: Resultsmentioning
confidence: 99%